Timing of Repetitive Transcranial Magnetic Stimulation Onset for Upper Limb Function After Stroke: A Systematic Review and Meta-Analysis - van Lieshout, Eline C. C.; van der Worp, H. Bart; Visser-Meily, Johanna M. A.; Dijkhuizen, Rick M. (Frontiers in Neurology, 2019)
Background. Repetitive transcranial magnetic stimulation (rTMS) is a promising intervention to promote upper limb recovery after stroke. We aimed to identify differences in the efficacy of rTMS treatment on upper limb function depending on the onset time post-stroke. Methods. We searched PubMed, Embase, and the Cochrane Library to identify relevant RCTs from their inception to February 2018. RCTs on the effects of rTMS on upper limb function in adult patients with stroke were included. Study quality and risk of bias were assessed independently by two authors. Meta-analyses were performed for outcomes on individual upper limb outcome measures (function or activity) and for function and activity measures jointly, categorized by timing of treatment initiation. Timing of treatment initiation post-stroke was categorized as follows: acute to early subacute (<1 month), early subacute (1-3 months), late subacute (3-6 months) and chronic (>6 months). Results. We included 38 studies involving 1074 stroke patients. Subgroup analysis demonstrated benefit of rTMS applied within the first month post-stroke (MD=9.31; 95% confidence interval [6.27-12.34]; P<.0001), but not in the early subacute phase (1-3 months post-stroke) (MD=1.14; 95% confidence interval [-5.32-7.59], P=.73) or chronic phase (>6 months post-stroke) (MD=1.79; 95% confidence interval [-2.00-5.59]; P=.35), when assessed with a function test (Fugl-Meyer Arm test (FMA)). There were no studies within the late subacute phase (3-6 months post-stroke) that used the FMA. Tests at the level of function revealed improved upper limb function after rTMS (SMD=0.43; 95% confidence interval [0.02-0.75]; P=.0001), but tests at the level of activity did not, independent of rTMS onset post-stroke (SMD=0.17; 95% confidence interval [-0.09-0.44]; P =.19). Heterogeneities in the results of the individual studies included in the main analyses were large, as suggested by funnel plot asymmetry. Conclusions. Based on the FMA, rTMS seems more beneficial only when started in the first month post-stroke. Tests at the level of function are likely more sensitive to detect beneficial rTMS effects on upper limb function than tests at the level of activity. However, heterogeneities in treatment designs and outcomes are high. Future rTMS trials should include the FMA and work towards a core set of outcome measures.